Design and antiviral assessment of a panel of fusion proteins targeting human papillomavirus type 16. - Chongzhi Bai; Ruoyu Wang; Qian Yang; Jianqing Hao; Qiming Zhong; Ruiwen Fan; Pengcheng Han (PLoS ONE)
Cervical cancer ranks as the third most prevalent malignancy in women worldwide. The persistence of Human papillomavirus (HPV) infection stands out as the foremost risk factor for cervical cancer development. Among the numerous HPV subtypes, HPV16 infection emerges as the primary pathogenic determinant of cervical cancer. To date, no specific drugs have been approved. In this study, we engineered two high-affinity fusion protein targeting HPV16 L1 protein based on the alpaca-derived single-domain antibody 2C12 previously obtained in our laboratory. These two fusion proteins exhibited potent neutralizing activity against HPV16 pseudovirus with IC50 values of 7.8 nM and 6.5 nM, respectively. Molecular docking analysis revealed that 2C12 formed ten pairs of hydrogen bonds with HPV16 L1, among which Arg39 and Thr100 established multiple pairs of hydrogen bonds with HPV16 L1, indicating their crucial roles in antigen-antibody binding process. These structural and biological findings underscore the effective binding capacity of these fusion proteins to HPV16, leading to reduced viral load and providing valuable insights into therapeutic antibody and vaccine development against HPV 16 infection.